Cold-induced serum short-chain fatty acids act as markers of brown adipose tissue metabolism in humans - Monfort-Pires, Milena; U-Din, Mueez; de Mello, Vanessa; Saari, Teemu; Raiko, Juho; Kerminen, Edla; Rajander, Johan; Hanhineva, Kati; Fromme, Tobias; Landberg, Rikard; Klingenspor, Martin; Virtanen, Kirsi A. (Oxford University Press, 2026)
Background
Short-chain fatty acids (SCFAs) produced from dietary fibre fermentation can regulate adipose tissue metabolism through signalling pathways involving G-protein-coupled receptors and histone deacetylase inhibition. While preclinical studies suggest they enhance thermogenesis, their role in human brown adipose tissue (BAT) under different thermal conditions remains unclear.
Objective
This study explores the associations between circulating SCFAs and human BAT metabolism at room temperature and after cold exposure.
Methods
This cross-sectional study included data from 71 adults (20–55 years, BMI 19–44 kg/m²). Dynamic [15O]O2, [15O]H2O, [¹⁸F]FDG, and [¹⁸F]FTHA PET/CT scans were used to assess BAT metabolism. Serum SCFAs were quantified using LC-MS, and gene expression in biopsy-excised BAT samples (n=14) was analysed. Participants were stratified into low- and high-BAT groups based on [¹⁸F]FDG or [¹⁸F]FTHA uptakes.
Results
Cold-induced acetate and propionate were positively associated with key in vivo BAT metabolism indicators, namely non-esterified fatty acids (NEFA) uptake and oxygen consumption. Only in the high-BAT group were circulating SCFAs maintained after cold exposure. BAT transcriptome revealed that genes involved in SCFA metabolism (such as conversion to acetyl-CoA) correlated with thermogenic and lipid metabolism genes exclusively in the high-BAT group, suggesting a distinct molecular link between SCFA pathways and BAT function.
Conclusion
Circulating SCFAs are linked with BAT oxidative metabolism and NEFA uptake during cold exposure. The observed correlations between SCFA catabolic genes and thermogenic markers suggest that metabolically active BAT may selectively engage SCFA-related pathways, pointing to a potential mechanistic role of SCFAs in supporting BAT function in humans.